Solid waste management in Nigeria: problems, prospects, and policies - Ike, C. C.; Ezeibe, C. C.; Anijiofor, S. C.; Daud, N. N. Nik (Journal of Solid Waste Technology and Management, 2018)
Solid waste management is a major environmental challenge in most Nigerian cities. Waste generation rate in Nigeria is estimated at 0.65-0.95 kg/capita/day which gives an average of 42 million tonnes of wastes generated annually. This is more than half of 62 million tonnes of waste generated in sub-Sahara Africa annually and where and how to channel these wastes becomes a huge problem for the nation. This study examines the problems and prospects of solid waste management in some selected Nigerian cities using the mixed method of data collection. The findings revealed that waste management in Nigerian cities is largely monopolized by the agencies of state governments (sub-national governments) which have limited capacity to tackle the problems of solid waste management in their cities. In addition, 52 % of wastes generated are organic wastes which creates additional disposal problems. Although the problems of solid waste management in Nigeria range from poor collection and disposal methods; lack or poor waste management database; insufficient financial resources; non-compliance to laws and lack of awareness on dangers of poor sanitary habits, this paper argues that a robust waste data base, strict policies and regulation are important for effective solid waste management in Nigeria.